HASIL BELAJAR FISIKA MODEL PEMBELAJARAN LESSON STUDY DAN KOOPERATIF TYPE STAD SISWA MAN 1 KONAWE SELATAN - Syafrial Syafrial (Institut Agama Islam Negeri Kendari, 2017)
This study aims to know the students’ learning achievement after studying under Lesson Study learning model at MAN 1 Konawe Selatan, under cooperative learning model type STAD and to investigate the significant difference between Lesson Study learning model and cooperative learning model type STAD. The subject of the study is the students of MAN 1 Konawe Selatan class XI IPA. This study is a quasi experimental research which means that it is not a real experimental research because it included the basic steps of experiment but exclude the control class. The result indicates that there is different students’ physics learning achievement between using Lesson Study learning model and coopertive learning model type STAD. The students learning under lesson study model obtained 87 as their average score, while those with cooperative model type STAD obtained 67.3. In other words, learning by lesson plan model contributes more positively to students’ learning achievement than STAD model. This indicates that there are differences in physiscs learning achievement between lesson study learning model and cooperative learning model type STAD at students class XI-Science MAN 1 South of Konawe